Physiological roles of CNS muscarinic receptors gained from knockout mice. (1st July 2018) - Thomsen, Morgane; Sørensen, Gunnar; Dencker, Ditte
Abstract: Because the five muscarinic acetylcholine receptor subtypes have overlapping distributions in many CNS tissues, and because ligands with a high degree of selectivity for a given subtype long remained elusive, it has been difficult to determine the physiological functions of each receptor. Genetically engineered knockout mice, in which one or more muscarinic acetylcholine receptor subtype has been inactivated, have been instrumental in identifying muscarinic receptor functions in the CNS, at the neuronal, circuit, and behavioral level. These studies revealed important functions of muscarinic receptors modulating neuronal activity and neurotransmitter release in many brain regions, shaping neuronal plasticity, and affecting functions ranging from motor and sensory function to cognitive processes. As gene targeting technology evolves including the use of conditional, cell type specific strains, knockout mice are likely to continue to provide valuable insights into brain physiology and pathophysiology, and advance the development of new medications for a range of conditions such as Alzheimer's disease, Parkinson's disease, schizophrenia, and addictions, as well as non-opioid analgesics. This article is part of the Special Issue entitled 'Neuropharmacology on Muscarinic Receptors'.